Synthesis and evaluation of anti-tyrosinase activity of phenyl benzyl ether derivatives: Effects of functional groups and their positions - Suttisintong, Khomson; Palakhachane, Sarinya; Athipornchai, Anan; Pimtong, Wittaya; Limpachayaporn, Panupun (Science, Engineering and Health Studies, 2018)
Thirteen phenyl benzyl ethers were synthesized and their in vitro inhibitory activity towards tyrosinase, rate-determining enzyme in melanogenesis, was evaluated. The results showed that p-substituted phenyl benzyl ethers, especially p-chlorophenyl ones (23), exhibited significantly higher inhibition percentage to the ethers substituted at meta- and ortho-positions at 500 µM. At the same concentration, polysubstituted phenyl benzyl ethers 31 and 32 exhibited comparable inhibition percentage to kojic acid. Furthermore, p-chlorophenyl (23) and tribrominated phenyl analogues (32) were proven to have similar and even higher inhibition potency compared to kojic acid (IC50 = 106 µM) with IC50 of 55.7 and 93.8 µM, respectively. This study suggested that phenyl benzyl ethers 23 and 32 might be promising candidates for skin whitening agents for pharmacological and cosmetical products.